(untitled) (AYUSHDHARA, 2018)
Toxic or nutritional optic neuropathy, also known as toxic amblyopia, is basically a chronic retrobulbar neuritis, wherein visual loss results from damage to the optic nerve fibers due to the effects of exogenous or endogenous causes. It is frequently bilateral and has a chronic course with permanent visual deterioration. Under the varieties of various toxic amblyopia, this case is more towards the amblyopia which is caused by the diet deficient in proteins and vitamin B complex. The condition is characterized by impairment of central vision, which is bilateral and gradually progressive. Patients usually complain of fogginess of vision and difficulty in doing near work. Clinical features of nutritional optic neuropathy simulate the disease Dhumadarshi. In Ayurvedic classics our ancient seers have mentioned Dhumapana and Madhyapana as some of the etiological factors resulting in eye diseases and also Acharya Dalhana has clearly explained about Upabrumhaka rasa kshaya leading to Drushtigata rogas. Under treatment in allied sciences, complete cessation of tobacco, nutritional supplements, care of general health are the main modalities of treatments where in it implies the importance of Ahara, Dinacharya, Swastavrutta told in our classics. A male patient aged about 31 years approached our OPD with gradual visual loss from the past 1 year. On fundoscopic examination bilateral temporal disc pallor was noted and was diagnosed as a case of nutritional optic neuropathy and treated appropriately by adopting the classical line of treatment like Shodhana, Kriyakalpa, Rasayanas which has given a promising result in treating the case.